RISK FACTORS FOR ACUTE MYOCARDIAL INFARCTION IN THE REPUBLIC OF SERBIA - Matić, Marija (HEALTH CARE, 2026)
Background/Aim: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality from cardiovascular diseases (CVD) globally. The development of the disease is strongly associated with the presence and interaction of multiple risk factors – non-modifiable (sex, age, family history) and modifiable (hypertension, dyslipidemia, smoking, obesity, physical inactivity, diabetes mellitus, stress). The aim of this study is to analyze the prevalence of key risk factors for AMI among patients with acute coronary syndrome (ACS) treated in coronary care units in the Republic of Serbia (2006–2011), as well as in the general population of Serbia (2012–2022). Furthermore, these findings are compared with European and global averages to better understand the burden of risk factors and provide additional insight into the need for improved national preventive interventions. Methods: A descriptive epidemiological study was conducted. Data on the prevalence of risk factors in hospitalized patients with acute coronary syndrome (ACS) for the period 2006–2011 were retrieved from the annual publications of the "Dr Milan Jovanović Batut" Institute of Public Health of Serbia – the National Registry for Acute Coronary Syndrome. The prevalence of the same risk factors in the general population of the Republic of Serbia for the period 2012–2022 was analyzed using national and international secondary data sources, including reports from the World Health Organization (WHO), the Global Adult Tobacco Survey (GATS), the Global Burden of Disease Study (GBD), the National Health Surveys from 2013 and 2019, and the European Health Interview Survey (EHIS). Risk factors were defined in accordance with the methodology of the data sources used and current international guidelines. Results: A high prevalence of all analyzed risk factors was recorded among patients with ACS hospitalized in coronary care units in the Republic of Serbia. In 2011, approximately 35% of patients were recorded as smokers at the time of hospitalization (active smokers), about 73% had arterial hypertension, approximately 28% had diabetes mellitus, about 20% had obesity (BMI ≥30 kg/m²), and roughly 37% were physically inactive. More than half had dyslipidemia and a positive family history, while approximately 31% reported elevated psychosocial stress. Trend analysis for the 2012–2022 period indicates persistently high values of these modifiable risk factors in the general population, which match or exceed the levels recorded among hospitalized ACS patients in the preceding period. Conclusion: The findings of this study indicate a persistently high prevalence of modifiable risk factors in the Republic of Serbia, which transitioned from the ACS patient population (2006–2011) to the general population over the following decade (2012–2022). These trends, which are more unfavorable than the European average, highlight the urgent need for integrated preventive strategies targeting modifiable risk factors to reduce the overall cardiovascular burden in the Republic of Serbia.